High Prevalence of Multidrug-Resistant Klebsiella pneumoniae Harboring Several Virulence and β-Lactamase Encoding Genes in a Brazilian Intensive Care Unit - Ferreira, Roumayne L.; da Silva, Brenda C. M.; Rezende, Graziela S.; Nakamura-Silva, Rafael; Pitondo-Silva, André; Campanini, Emeline Boni; Brito, Márcia C. A.; da Silva, Eulália M. L.; Freire, Caio César de Melo; Cunha, Anderson F. da; Pranchevicius, Maria-Cristina da Silva (Frontiers in Microbiology, 2019)
Klebsiella pneumoniae is an important opportunistic pathogen that commonly causes nosocomial infections and contributes to substantial morbidity and mortality. We sought to investigate the antibiotic resistance profile, pathogenic potential and the clonal relationships between K. pneumoniae (n=25) isolated from patients and sources at a tertiary care hospital's intensive care units (ICUs) in the northern region of Brazil. Most of K. pneumoniae isolates (n=21, 84%) were classified as multidrug resistant (MDR) with high-level resistance to β-lactams, aminoglycosides, quinolones, tigecycline, and colistin. All the 25 isolates presented Extended-spectrum beta-lactamase-producing (ESBL), including carbapenemase producers, and carried the blaKPC (100%), blaTEM (100%), blaSHV variants (n=24, 96%), blaOXA-1 group (n=21, 84%) and blaCTX-M-1 group (n=18, 72%) genes. The K2 serotype was found in 4 % (n=1) of the isolates, and the K1 was not detected. The virulence-associated genes found among the 25 isolates were mrkD (n=24, 96%), fimH-1(n=22, 88%), entB (100%), iutA (n=10, 40%), ybtS (n=15, 60%). The genes related with efflux pumps and outer membrane porins found were AcrAB (100%), tolC (n=24, 96%), mdtK (n=22, 88%), OmpK35 (n=15, 60%), and OmpK36 (n=7, 28%). ERIC-PCR was employed to determine the clonal relationship between the different isolated strains. The obtained ERIC-PCR patterns revealed that the similarity between isolates was above 70%. To determine the sequence types (ST) a multilocus sequence typing (MLST) assay was used. The results indicated the presence of high-risk international clones among the isolates. In our study, the wide variety of MDR K. pneumoniae harboring β-lactams and virulence genes strongly suggest a necessity for the implementation of effective strategies to prevent and control the spread of antibiotic resistant infections.